Complications and Cost Analysis of Intraoperative Arterial Complications in Head and Neck Free Flap Reconstruction - Chang, Catherine S.; Chu, Michael W.; Nelson, Jonas A.; Basta, Marten; Gerety, Patrick; Kanchwala, Suhail K.; Wu, Liza C. (Journal of Reconstructive Microsurgery, 2017)
Background Microvascular anastomotic patency is fundamental to head and neck free flap reconstructive success. The aims of this study were to identify factors associated with intraoperative arterial anastomotic issues and analyze the impact on subsequent complications and cost in head and neck reconstruction.Methods A retrospective review was performed on all head and neck free flap reconstructions from 2005 to 2013. Patients with intraoperative, arterial anastomotic difficulties were compared with patients without. Postoperative outcomes and costs were analyzed to determine factors associated with microvascular arterial complications. A regression analysis was performed to control for confounders.Results Total 438 head and neck free flaps were performed, with 24 (5.5%) having intraoperative arterial complications. Patient groups and flap survival between the two groups were similar. Free flaps with arterial issues had higher rates of unplanned reoperations (p < 0.001), emergent take-backs (p = 0.034), and major surgical (p = 0.002) and respiratory (p = 0.036) complications. The overall cost of reconstruction was nearly double in patients with arterial issues (p = 0.001). Regression analysis revealed that African American race (OR = 5.5, p < 0.009), use of vasopressors (OR = 6.0, p = 0.024), end-to-side venous anastomosis (OR = 4.0, p = 0.009), and use of internal fixation hardware (OR =3.5, p = 0.013) were significantly associated with arterial complications.Conclusion Intraoperative arterial complications may impact complications and overall cost of free flap head and neck reconstruction. Although some factors are nonmodifiable or unavoidable, microsurgeons should nonetheless be aware of the risk association. We recommend optimizing preoperative comorbidities and avoiding use of vasopressors in head and neck free flap cases to the extent possible.
Keywords: head and neck reconstruction; arterial thrombosis; cost analysis